Is Awareness Enough to Change Consumer Behavior? The Moderating Role of Social Norms in Sustainable Behavior - Abu Bakar Ashidiqy; Meutia Riany; Andri Ardhiyansyah (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
Household waste management remains a significant environmental issue in Indonesia, particularly in urban regions such as West Java. There have been increased public campaign and environmental education efforts, but it does not always mean behavioral change in adopting sustainable consumption patterns. This study investigates the impact of environmental concern on environmentally responsible consumer behavior and the moderating role of social norms, and analyzes three antecedents of environmental concern: consumer education, influencer credibility, and product information clarity. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 230 West Java consumers at household level using online and offline questionnaires. The results indicate that environmental awareness plays a significant role in sustainable behavior, and social norms positively moderate this effect. In addition, consumer education, influencer credibility, and product information quality all play a significant role in the formation of environmental awareness. The findings endorse the relevance of the Theory of Planned Behavior (TPB) for understanding sustainable consumption and offer an integrative model consolidating the cognitive, communicative, and normative dimensions. This study presents pragmatic takeaways for campaign developers and policymakers both, pointing out that it's not only a matter of awareness but also shaping facilitative social environments to drive long-term behavior change.